Influence of environmental temperature on the hand-feel perception of textiles - Lars Claussen; Kimberly Lim; Julia Wilfling; Alex Lloyd; Daniel Ruiz; George Havenith (Communications in Development and Assembling of Textile Products)
The present study investigated the effect of environmental temperature on the hand-feel perception of textiles. Participants were exposed to three different climate conditions (10 °C/20 °C/ 30 °C, RH 65 %) to simulate cool, mild, and warm environments. Hand-feel attributes, comfort, and preferences of a wide range of textiles were rated by the participants. Participants’ body responses to the different temperatures were controlled by monitoring participants’ aural temperature, mean skin temperature, hand temperature, tactile sensitivity, and environmental perception. Fabric weight was measured to monitor changes in textile properties induced by the different environmental conditions. The outcomes of the study suggest that the environmental temperature led to significant changes in participants’ aural temperature, mean skin temperature, hand temperature, tactile sensitivity, and environmental perception, affecting the hand-feel perception of the different textiles. Thus, the present study provides insight for practitioners to develop more comfortable textiles for specific environmental temperatures by establishing a basis for understanding how environmental temperature, body responses, and hand feel perception interact.